The Role of the Dental Surgeon in Controlling the Dissemination of COVID-19: A Literature Review - Régida C. S. Batista; Caio V. B. Arruda; Marcely Cassimiro; Luciana Gominho; Antônio Carlos Moura; Diana S. Albuquerque; Kaline Romeiro (The Scientific World Journal)
As early as December 2019 in the province of Hubei, China, contamination of patients with pneumonia of an unknown etiology occurred. These patients presented with symptoms such as coughing, sore throat, malaise, diarrhea, high fever, and dyspnea. This emerging disease was named COVID-19 due to being part of the group of coronaviruses (CoVs) belonging to the subfamily Orthocoronavirinae, in the Coronaviridae family and in the Nidovirales order. COVID-19 is most commonly transmitted through speech, coughing, sneezing, and salivary sputum. Because dental professionals work closely with the oral cavity, it is imperative that infection prevention controls are strictly adhered to. It is important that the dental profession treats patients while also limiting the possible contamination through the production of aerosol in the dental environment. Furthermore, the dental professional also has a key role in raising awareness and guidance amongst the population concerning COVID-19 related biosafety measures. This literature review aims to inform dental professionals about the COVID-19 pandemic and to present the implications of the virus to the dentist. Dental professionals are considered to be at high risk for contracting SARS-CoV-2.